Green and Blue Economy Concept Analysis: Ujung Kulon National Park (TNUK) Ecotourism - Risnawijaya, Ris (Electronic Journal of Education, Social Economics and Technology, 2024)
Global warming has become a major challenge faced by all countries, including Indonesia. Deforestation is one of the causes that exacerbates global warming. Ujung Kulon National Park (TNUK) plays an important role in nature conservation and ecotourism, making sustainable ecosystem management in the TNUK area. This research aims to explore the application of green and blue economies in ecotourism management in TNUK and assess their impact on the welfare of the local community. The method used is a qualitative descriptive approach with data collection through document studies from various relevant sources. The research results show that although TNUK has been successful in conservation, such as the increase in the Javan rhinoceros population, the potential of ecotourism has not been optimized in boosting the local economy. This is due to the limited infrastructure and public facilities in the areas surrounding TNUK. As a result, despite TNUK's significant tourist appeal, its contribution to poverty and unemployment reduction remains limited. This research recommends improving infrastructure and fostering cooperation between the government and the community to optimize the benefits of ecotourism.